2003
DOI: 10.1103/physrevb.68.035332
|View full text |Cite
|
Sign up to set email alerts
|

Edge reconstructions in fractional quantum Hall systems

Abstract: Two dimensional electron systems exhibiting the fractional quantum Hall effects are characterized by a quantized Hall conductance and a dissipationless bulk. The transport in these systems occurs only at the edges of the incompressible quantum Hall regions, where gapless excitations are present. We present a microscopic calculation of the edge states in the fractional quantum Hall systems at various filling factors using the extended Hamiltonian theory of the fractional quantum Hall effect. We find that at ν =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…The latter one was recently observed via shot noise measurements [16][17][18] and also by heating a narrow constriction [16,[19][20][21]. Noting that for a sufficiently shallow confining potential near the edge, edge reconstruction was predicted to take place also in a variety of non-hole-conjugate fractional states [22][23][24][25][26][27][28][29] (neutral modes had been recently found in electronlike fractional states [18]) and even in integer fillings [30].…”
mentioning
confidence: 78%
“…The latter one was recently observed via shot noise measurements [16][17][18] and also by heating a narrow constriction [16,[19][20][21]. Noting that for a sufficiently shallow confining potential near the edge, edge reconstruction was predicted to take place also in a variety of non-hole-conjugate fractional states [22][23][24][25][26][27][28][29] (neutral modes had been recently found in electronlike fractional states [18]) and even in integer fillings [30].…”
mentioning
confidence: 78%
“…[40]. We mention that a sharp confining potential may also be beneficial for measuring interference at the ν = 1/3 state by preventing edge reconstruction and the proliferation of neutral edge modes [20,47,48] which may cause dephasing [49,50]; neutral modes have been detected at ν = 1/3 and numerous other fractional quantum Hall states in standard GaAs structures without screening wells [51].…”
Section: Fractional Quantum Hall Regimementioning
confidence: 97%
“…It is found that at ν = 1/3 the quantum Hall edge undergoes a reconstruction as the background potential softens, whereas quantum Hall edges at higher filling factors are robust against reconstruction. 10 Since the edge physics at ν = 1/3 is not confined to the boundary but extends to the bulk, we should consider our results within a specific range. 11 However, as the size of the droplet varies as R ∼ √ N, it is expected that the situation will improve for large N .…”
Section: Numerical Resultsmentioning
confidence: 99%